-2(-x-1)=12

Simple and best practice solution for -2(-x-1)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-x-1)=12 equation:


Simplifying
-2(-1x + -1) = 12

Reorder the terms:
-2(-1 + -1x) = 12
(-1 * -2 + -1x * -2) = 12
(2 + 2x) = 12

Solving
2 + 2x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 2x = 12 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = 12 + -2
2x = 12 + -2

Combine like terms: 12 + -2 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| 2n^2+5n+3=0 | | 2n+4n=3n-2 | | d=-(-6-4x)-(1+9x) | | 9x-164=3x-8 | | 5x-15y+ax-3ay=0 | | 20=7+p | | 132-3x=24x+21 | | 3y(y-7)-4(y-7)=0 | | -(x-4)+2=13 | | 4x^2-11x+8=6x+4 | | (6x-3)2=(4x+7)3 | | 3x=5(x-6) | | 27+u=3-3u | | 2(5+x)=150 | | 7-1x=4+x | | x^4-9x^3+27x^2-15x-52=0 | | X=45-4x | | 7-x+2=2x-12 | | 9x^2+17=71 | | 0=8t | | -x^2+9x=18 | | 6x^2-12x=-1 | | -7x=2x+3 | | 3m-2=-5m+9 | | x-8.8=-6.9 | | -6x+24=18 | | 15X+100000=14x+200000 | | 2b+6a=14 | | 4(x)-24=-20 | | 3(x-3)=-6 | | -x^2+11x=18 | | 3a+4b-5c=0 |

Equations solver categories